2019
DOI: 10.1111/ajt.15525
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear relationship between visceral adipose tissue and frailty in adult lung transplant candidates

Abstract: Frailty is a state of decreased physiologic reserve associated with poor outcomes before and after lung transplantation. Obesity, particularly central obesity characterized by excess proinflammatory visceral adipose tissue (VAT), is associated with incident frailty in middle-aged and older adults. The association between VAT and frailty in advanced lung disease, however, is unknown. In two, nonoverlapping multicenter cohorts of adults listed for lung transplantation, we measured VAT area on bioelectrical imped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…[21] observed that increased SAT from a single thoracic axial slice was associated with improved post‐transplant three‐year survival, whereas Gonzalez et al observed a lower three‐year survival with increased mediastinal fat volume, and no association was seen in the other two studies evaluating SAT and VAT [22,56]. In two of the studies, increased SAT on abdominal CT and increased mediastinal fat volumes were associated with a higher risk of developing PGD [33,56]. This supports the notion that abdominal SAT and mediastinal adipose tissue is associated with an increased inflammatory milieu [57] characterized by increased reactive oxygen species and decreased clearance of circulating fatty acids, both risk factors for accumulation of ectopic adiposity and PGD [58,59].…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…[21] observed that increased SAT from a single thoracic axial slice was associated with improved post‐transplant three‐year survival, whereas Gonzalez et al observed a lower three‐year survival with increased mediastinal fat volume, and no association was seen in the other two studies evaluating SAT and VAT [22,56]. In two of the studies, increased SAT on abdominal CT and increased mediastinal fat volumes were associated with a higher risk of developing PGD [33,56]. This supports the notion that abdominal SAT and mediastinal adipose tissue is associated with an increased inflammatory milieu [57] characterized by increased reactive oxygen species and decreased clearance of circulating fatty acids, both risk factors for accumulation of ectopic adiposity and PGD [58,59].…”
Section: Discussionmentioning
confidence: 76%
“…The analysis of CT morphometrics beyond muscle mass measurements is gaining increased recognition, as obesity has been shown to be associated with increased levels of inflammation, adipokines, and cellular senescence [54–56]. In the present review, four studies evaluated the association of adiposity tissue with post‐transplant survival with heterogeneous results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations